Proposed Draft Medical Committee Letter
This proposed draft of a Medical Committee campaign letter urges support for Jane Tolmach in the Ventura County Assembly race, arguing that the State Legislature is overly dominated by lawyers. While acknowledging the importance of the legal profession, the letter notes that lawyers comprise over 30% of the Assembly and 45% of the Senate, raising concerns about overrepresentation and potential conflicts of interest. It presents Tolmach as an experienced local public servant respected across party lines and better suited to provide balanced representation. The letter concludes by requesting financial contributions and describing support for Tolmach as an investment in good government.